The influence of capital structure, liquidity, and hedging on company value in con sumer non-cyclical sector companies - Nadia, Zalfa; Khrisna Mahardika, Dewa Putra (Institute of Computer Science (IOCS), 2024)
Company value is investors' perception of the company's level of success which is related to share prices. A high share price will increase the company value and increase investor confidence. This research aims to determine the influence of capital structure, liquidity and hedging on company value in non-cyclical consumer companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2021 period. The sampling technique used in this research was purposive sampling based on certain criteria to obtain 216 observation data. This research is quantitative research with secondary data. The method used is panel data regression analysis. The research results show that capital structure (DER), liquidity (CR), and hedging do not simultaneously influence firm value (Tobin's Q). Partially, capital structure and liquidity influence company value. Meanwhile, hedging has no effect on company value.